Recent Advances Of Two-Dimensional-Based (2D) Materials As Electrocatalysts In Dlfc: An Overview - Zatil Amali Che Ramli; Jagadeesh Pasupuleti; Salma Samidin; Tengku Shafazila Tengku Saharuddin; Wan Nor Roslam Wan Isahak; A.G.N. Sofiah; S.P. Koh; Sieh Tiong Kiong (Elsevier, 2026)
Indexed by WOS / SCOPUS